Comparative study of gill, kidney and liver structure of Pangasius hypophthalmusreared under manipulated photoperiod and from the Siak River - Theresia Fanta Ria; Windarti Windarti; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractPangasiushypophthalmus is nocturnal fish that grow well in dark condition. In dark condition however, phytoplankton may be none, the water become rich in organic materials and this condition is match for developing parasites and pathogen that negatively affect the fish. Tounderstand the health status of the fish in general, the histologcal structure gill, kidney and liver was investigated. The results were then compared to those obtained from fish taken from the Siak River. The research was conducted on Agustus-Desember 2019. There were 4 treatments applied, namely control (natural photoperiod), 18G(18 hours dark ) and 24G (24 hours dark), 3 repetitions/ treatment. Parameters measured were survival rate and the histological structure (gills, kidneys and liver). Samples were fixed in 5% formalin and histologically processed and stained with Haematoxylin Eosin. Results shown that in general the histological structure (gill, kidney and liver) of the treated fish and the fish from the Siak River are not different. There were abnormalities in the gill, such as hyperplasia, hypertrophy, odema and necrosis. Inthe all fish there are Dactylogyrus sp parasites that may caused the gill damage. The histological structure of kidney and liver are normal. Data obtained indicate that the damage of the gill may caused by the presence of the parasite and it is not affected by the manipulated photoperiod. Keywords: Health Status, Siak River, Histological Structure, Dactylogyrus sp.